Розробка компонентів інформаційної системи обліку переглянутих серіалів - Колокольчева, С. А. (ХНУРЕ, 2025)
This work is devoted to creating a system for accounting of watched series, which allows users to conveniently manage their lists of series. Users can add series to the categories "watched", "want to watch" and "watching", rate them, as well as watch other users' lists. The system provides the abilІТy to track viewing progress, receive recommendations based on preferences and analyze watched content. The main goal of the development is to provide a convenient tool for planning series viewing and improving the user experience in working wІТh media content.
Keywords: облік серіалів; accounting of watched series